Does the system of supports and safeguards implemented in the Civil Code really fulfill its function of supporting people with disabilities? - Duran Vivanco, José William (2020)
In the present article, seeking to recognize the legal capacity of persons with disabilities, we express our conformity with the fact that the legislation reflects the social model contemplated in the International Convention on the Rights of Persons with Disabilities, since it contributes to enabling these persons to exercise their rights freely and voluntarily, with the cooperation of supporters. However, the objectives and principles established in the convention have not been adequately established in our legislation, and consequently, legislative measures have been adopted without prior consideration of our reality. For example, the recognition of the power to make one,s own decisions for people with disabilities who lack discernment leads to a series of abuses against them. In fact, this formula recognizes discernment but thus the lack of notion of the reality of these subjects.